The French Clergy and the Removal of Jesuits from Secondary Schools, 1761–1762 - Bailey, Charles Randall (Church history, 1979)
The Society of Jesus was a consistently controversial institution in France after papal confirmation of the order in 1540 and its installation in Paris shortly afterward. As early as 1562 a jealous University of Paris challenged, unsuccessfully, the right of its members to teach. They became embroiled in political matters from the first. King Henry IV and the Parlement of Paris, the most important law court of the realm, cooperated in exiling them from France between 1594 and 1603 because of their political intrigues.